A Comparative Change in Left Ventricular Mass Index on Echocardiography in Hypertensive Diabetic and Non-Diabetic Patients Taking Candesartan - Tayyaba Nasir, Sakhawat Abbas, Umar Khalil, Tehreem Nasir, Muhammad Kaleem, Muhammad Shahzad Aslam, Umair Khalid, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: To assess the evolution of the left ventricular mass index on echocardiography in candesartan-treated hypertension individuals with and without diabetes. Study Design: This is a cross-sectional comparative study. Practical Implications: In the current study there was an echocardiographic comparison of left ventricular mass index changes in both diabetic and non-diabetic hypertensive patients was concluded with candesartan cilexetil. The findings of this clinical trial are so beneficial for hypertensive patients to manage their self. Keywords: Hypertensive, Diabetics, Candesartan and Left ventricular index, posterior wall thickness.